Investigating the Causative Factor of Musculoskeletal Injury for Indonesian Traditional Martial Arts - Kusuma, Moh Nanang Himawan; Novita (Physical Education Theory and Methodology, 2023)
Background. The interest in Pencak Silat is growing significantly, however, followed by the elevation of injury cases with 7.7% for females and 17.8% for males. Study purpose. The study explores the injuries profile of musculoskeletal, including type, form, location, mechanism, and risk factors, across genders. Materials and methods. Two hundred and twenty-nine athletes including 148 males and 81 females in 4 different Sports Schools and Clubs (age 21.3±3.7 years old, BMI 21.12±1.56 kg/m², normal resting heart rate), who had ever attended the national competition, voluntarily participated. The personal data was collected by a research assistant, the training load was recorded by coaches, while the injuries profile was legitimated with the OSTRC-Questionnaire by medical rehabilitation specialists, and Postural Investigation was confirmed by certified clinical staff with FMS-Score-test. Results. The Incidence Rate (IR) for males was higher with 48.5 (95% CI: 45.8–51.3) and was 35.2 injuries/1000 hours for females, males had 3.1 times higher severity level than females (2.3±1.2) and had longer injuries duration (4.8±2.6 weeks) than females. The contusion brought the most frequent incidence at 32.9/1000 hours (36.7%), hematoma at 19.9 injuries/1000 hours (95%CI:17.9-23.1), and muscle soreness (12.1/1000 hours). The lower limbs were the most damaged areas with 33/1000 hours and the upper limbs (26,5%) with 5-14 injuries/1000 hours. The previous injury has a risk effect with 3.0 times higher contributed to the on-set current injury, followed by Excessive training. A kick by the opponent (25%) and offensive kick (19%) were a frequent mechanism of injuries. Conclusions. The Injury Rate (IR) was significantly different between the genders. The findings strengthen the study of injuries, which are specially characteristic of Pencak Silat, that may contribute to delivering injuries profile.